The Easter Sunday Attacks : Struggle for the Soul of Sri Lankan Muslims - Kumar Ramakrishna (2019)
The Sri Lankan government is banning the public wearing of the face-veil by some Muslim women as a security measure in the wake of the Easter Sunday attacks on churches and hotels claimed by ISIS. This is symptomatic of a deeper struggle: the battle to shape the soul of Sri Lankan Muslims. This has implications for countering future ISIS-type attacks.